Boosting English Motivation with Mobile Tech: Action Research Among Engineering Students - Kristiana Candrawati, Devi Ferera; Dwiyani Pratiwi; Yuyun Yulia (Universitas Hamzanwadi, 2024)
This study focuses on increasing the students’ motivation in learning English by using MALL. The research sample consisted of 29 students (21 male students and 8 female students) of twelfth-grade Computer and Network Engineering students. The form of this research was to investigate the impact on motivation levels of students in learning English using MALL applications and to reveal students’ responses from the students after they have been taught by using MALL applications in learning English. The MALL applications used in this research include Duolingo, DeepL, and Quizizz. This is classroom action research consists of three cycles with two meetings in each cycle, with three types of data collection: student achievement results, interviews, and classroom observations. The data were analyzed descriptively qualitative. The result showed that teaching utilizing the three MALL applications enhanced students' achievement scores from 60,5 to 80 based on their average daily score. The three cycles of study that have been done by researchers showed that students' motivation to learn English has developed significantly since the three MALL applications have been implemented in place. The interview and observation results highlighted participants' positive feedback on using MALL for English learning and evaluation. Students enjoyed and were motivated to regularly use MALL to improve their language skills. Classroom observations showed that 51.72% of students had no hesitation in utilizing MALL applications for English enhancement.